Modelling and Simulation of Filtration in the Development of Water Treatment Technologies - Wojciechowska, K. (Engineering Transactions, 2002)
The paper presents modelling and simulation of water filtration in a multilayer rapid filter. As far as modelling is concerned, a combination of phenomenological and theoretical models was described. Special attention is paid to modelling of the filter coefficient. The model developed is a basis for filtration simulation in the filter bed. Simulation results for the concentration of particles in the filtered water, concentration of particles deposited in the bed and the headloss in the bed are presented as 3D diagrams. They are consistent in quality with the values obtained in the physical process which is discussed in the analysis herein. Thus, it can be concluded that the model for the process was selected correctly, its parameters were set appropriately and the numerical solution of partial differential equations involved in the model was also correct. The developed numerical model may serve as a new tool for development of water treatment technologies. Numerical simulations were carried out, applying the "Mathematica" program.